Simulation of vermiform movements through random walks between n-simplex neighbors - Arroyo-Hernández, Jorge (2020)
Application of computational vision techniques in biological contexts usually requires manual annotation of data from the specific context, which makes these stages costly due to investment in specialized human resource time. In this article we present a novel method of generating random data within a subdomain restricted to a variety of allowed shapes. The process is particularized to explicit models based on border landmarks for vermiform structures. Through this process, sequenced deformations of worm movements are simulated by random walks between the subdomains.